Constitutional Integration of Customary Law in Criminal Case Handling Mechanisms Based on the National Criminal Code (Law Number 1 of 2023) - Tulia, Arter Lukas (Yayasan Cahaya Generasi Positif, 2025)
The reform of criminal law through Law Number 1 of 2023 concerning the Criminal Code marks a paradigm shift from a retributive approach to corrective, restorative, and rehabilitative justice. One important aspect of this reform is the constitutional recognition of living law, including customary criminal law. This recognition affirms that customary law has a legitimate position as a basis for criminal punishment, with criminal provisions that can be in the form of fulfilling local customary obligations. This study uses a normative juridical method with a statutory and conceptual approach to analyze how the integration of customary criminal law into criminal case handling mechanisms can be implemented constitutionally within the framework of the National Criminal Code. The results show that customary criminal cases are still handled within the general criminal justice system, without the establishment of a separate customary court. However, customary leaders play a crucial role as experts in explaining violated customary norms, while the resolution of cases is directed towards restorative justice that aligns with the principles of the 1945 Constitution and Pancasila. These findings confirm that the constitutional integration of customary law into the national criminal justice system is a crucial step in realizing substantive justice, legal pluralism, and harmonization between national law and local values ​​prevalent in society.